Analyzing the Direction of the Stock Exchange Cycle - Yulyanah, Yulyanah; Manurung, Adler Haymans (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research analyzes the direction of the stock market cycle and looks at the stock market prospects from January 2010 to September 2023. The methodology used in this research is the